Upaya Peningkatan Kemampuan Guru dalam Memanfaatkan Lingkungan Madrasah Sebagai Sumber Belajar Melalui Kegiatan Buzz Group Discussion Guru MIN 2 Kota Pasuruan - Siti Maryam (Universitas Nusantara PGRI Kediri, 2022)
This research was designed in the form of Madrasah Action Research which was planned to be carried out in two cycles. The subjects of this study were teachers at MIN 2 Pasuruan City, which consisted of six class teachers. Data collection techniques use observation and documentation techniques, while the data collection tools consist of observation formats for the implementation of discussion activities in small groups, learning scenario assessment formats, learning implementation assessment formats. Data validation uses the technique of extending the observation period, continuous observation and triangulation. The data analysis used was descriptive qualitative analysis by describing the qualitative data that was successfully collected at the initial observation stage and the observation stage of the implementation of the action. The results of the research show that the process of developing teachers' ability to use the environment as a learning resource at MIN 2 Pasuruan City through the implementation of small group discussions (buzz group discussions) is proven to be able to increase the ability to use the environment as a learning resource. This is evidenced by the increasing results of the assessment of the three aspects that are the focus of improvement. The results of the assessment of these three aspects showed that in the observation aspect of small group discussions, the average value was 64.17 with less criteria, increasing to 79.00 with sufficient criteria and 88.17 with good criteria in the last cycle. The aspect of preparing the learning scenario aspects of the assessment results showed a score of 61.67 in the initial conditions with less criteria, increased to 79.17 with sufficient criteria and in the last cycle to 86.67 with good criteria. The aspect of learning implementation from a score of 60, increased to 79.44 and 86.11 with an explanation of the value criteria from less, increased to sufficient and good in the last cycle. the components studied showed results above the success criteria of 85%. The conclusion is that through Buzz group discussion activities it is proven to be able to improve the ability of teachers at MIN 2 Pasuruan City Semester 1 of the 2017/2018 Academic Year in empowering the environment as a learning resource.